Engineering aortic valves via transdifferentiating fibroblasts into valvular endothelial cells without using viruses or iPS cells - Peng Tang; Fuxiang Wei; Weihua Qiao; Xing Chen; Chenyang Ji; Wanzhi Yang; Xinyu Zhang; Sihan Chen; Yanyan Wu; Mingxing Jiang; Chenyu Ma; Weiqiang Shen; et al. (Bioactive Materials)
The technology of induced pluripotent stem cells (iPSCs) has enabled the conversion of somatic cells into primitive undifferentiated cells via reprogramming. This approach provides possibilities for cell replacement therapies and drug screening, but the potential risk of tumorigenesis hampers its further development and in vivo application. How to generate differentiated cells such as valvular endothelial cells (VECs) has remained a major challenge.Utilizing a combinatorial strategy of selective soluble chemicals, cytokines and substrate stiffness modulation, mouse embryonic fibroblasts are directly and efficiently transdifferentiated into induced aortic endothelial cell-like cells (iAECs), or human primary adult fibroblasts are transdifferentiated into induced valvular endothelial cell-like cells (hiVECs), without expressing pluripotency stem cell markers. These iAECs and hiVECs express VEC-associated genes and proteins and VEC-specific marker NFATC1 and are functional in culture and on decellularized porcine aortic valves, like mouse aortic endothelial cells or human primary aortic valvular endothelial cells. The iAECs and hiVECs seeded on decellularized porcine aortic valves stay intact and express VEC-associated proteins for 60 days after grafting into abdominal aorta of immune-compromised rats. In contrast, induced pluripotent stem cells (iPSCs) are less efficient in differentiating into VEC-like cells and pluripotency marker Nanog is expressed in a small subpopulation of iPSC-derived VEC-like cells that generate teratomas in SCID mice whereas hiVECs derived from transdifferentiation do not generate teratomas in vivo. Our findings highlight an approach to efficiently convert fibroblasts into iAECs and hiVECs and seed them onto decellularized aortic valves for safely generating autologous tissue-engineered aortic valves without using viruses or first reprogramming the cells into pluripotent stem cells.